Polarimetry from the Stratosphere with Spider and BLASTPol - Shariff, Jamil Aly (2016)
This thesis presents the hardware development and flight performance of two balloon-borne experiments. The Spider experiment is a millimetre-wavelength polarimeter designed to measure B-mode polarization in the Cosmic Microwave Background at degree scales. This pattern is the imprint of the primordial gravitational waves predicted to have been produced by inflation. The BLASTPol experiment is a submillimetre-wavelength polarimeter designed to measure the linearly-polarized emission from aligned dust grains in Galactic molecular clouds, inferring the directions of the magnetic fields there. One goal of this measurement is to understand the role of magnetic fields in the earliest stages of star formation. Spider had a Long-Duration Balloon flight around Antarctica in January 2015. BLASTPol had two such flights, in December 2010 and 2012. Analysis of Spider data is underway. Results of BLASTPol 2012 data analysis are presented herein. The design and performance of the Spider pointing control system is presented. A new pivot motor control mode was developed, in which the servo drive controlled motor velocity, not current. This mode enabled sinusoidal azimuth scans at a peak speed of 5 deg/s, with a peak acceleration of 0.5 (deg/s)/s, in flight. The pointing stability in flight was 1'' to 2'' RMS. A new elevation drive system was designed and built for Spider. The Spider observing strategy is presented. It enabled observation of a 10% patch of sky, avoiding the sun and Galactic plane, with uniform coverage in declination, and good cross-linking. A model of the BLASTPol 2012 PSF was developed, allowing centroiding, flat-fielding, and map deconvolution. The latter was attempted in Fourier space, and using the Lucy-Richardson method. A net linear polarization of the dust emission in the Carina Nebula was measured by BLASTPol. The mean fractional polarization is 6.75% +/- 0.015%, 6.84% +/- 0.016% and 7.06% +/- 0.019%, at 250, 350, and 500 μm respectively. A falling polarization spectrum was found, in contrast with the V-shaped spectrum measured in other molecular clouds. The median ratios of the fractional polarization between bands have been measured to be 1.0155 +/- 0.00035 between 250 and 350 μm, and 0.9376 +/- 0.00056 between 500 and 350 μm. Ph.D.